Perceptions of Tutoring Students in Pekalongan on Interest in Continuing Higher Education at State Islamic Religious Universities: What and How - Nurul Husnah Mustika Sari; Arditya Prayogi; Fika Luthfia Sari (AL-ISHLAH: Jurnal Pendidikan, 2024)
In general, state Islamic religious universities (PTKIN) in Indonesia are still not the main choice for most high school and equivalent students in Indonesia, including in the city of Pekalongan and more specifically for tutoring students. On this basis, this article aims to reveal how their perceptions relate to their interest in continuing higher education at PTKIN. This research article is qualitative research using a case study approach with qualitative descriptive analysis. The research subjects in this study were managers of tutoring institutions and tutoring students in Pekalongan City. The sample in the research was taken using goal-oriented sampling or purposive sampling. Data collection in this research was carried out through documentation, questionnaires and interviews. The research results show that tutoring students in Pekalongan perceive PTKIN positively. The majority of these tutoring students have good knowledge and experience with PTKIN. However, even though the perception is positive, the research results show that this positive perception is not necessarily linear with interest.